Doing right for patients: A grounded theory on physicians' understanding and negotiation of ethical dilemmas - Estacio, Rhodora Carino (Animo Repository, 2013)
The purpose of this qualitative study was to explore how Philippine medical practitioners perceive and negotiate ethical dilemmas they encounter in the course of their clinical practice. The study used the grounded theory method of Glaser and Strauss (1967) and Strauss and Corbin (1990) with in-depth, semi-structured interviews to understand the lived experiences of twenty eight (28) participants whose age ranged from 27-70 years. After open coding of transcripts of interviews, axial coding and selective coding of emerged concepts, six distinct yet related categories were identified namely a.) the nature of an ethical dilemma, b.) causal conditions triggering the dilemmas, c.) contextual conditions of the ethical challenges, d.) intervening conditions affecting the negotiation of the dilemmas, e.) action/ strategies in resolving the dilemmas and f.) outcome/consequences of the decision on these ethical challenges. The core category of Doing Right for Patients was identified as the central theory that emerged. The study revealed that the processes could serve as a grounded typology in which physician participants gain a better hold of how they live, grasp, and deal with their decision-making regarding ethical dilemmas and what it means to do right for patients. The results of this study suggest that an understanding of the perceptions and negotiations of ethical dilemmas among physicians may lead to recognition and greater comprehension of their leadership role among other healthcare providers in the healthcare organizations. It also pointed to development of new models of medical ethics education that is more attuned to culture and context of Philippine society. Likewise, there is clear implication for educational leaders to seriously consider the inclusion of leadership-management courses in the medical curriculum.